The Influence of Service Quality and Price on Shopeefood Generation Z Customer Satisfaction in Bandung City - Melati Rahma Anggraeni; Deni Solihin (Takaza Innovatix Labs Ltd., 2026)
The rapid growth of online food delivery services like ShopeeFood in Indonesia motivates this study, as service quality and price are crucial for Generation Z customer satisfaction in Bandung City despite complaints about drivers and shipping costs. This explanatory quantitative research targets a population of 659,583 Generation Z users (born 1997-2012), with a sample of 100 respondents selected via Slovin formula and purposive sampling (minimum 3 uses/month). A 5-point Likert questionnaire (valid r>0.1966, reliable α>0.70) was analyzed descriptively, with classical assumption tests, multiple linear regression, and t-F tests using SPSS 27. Results show significant partial effects of service quality (β=0.173, t=11.926, p=0.000) and price (β=0.172, t=8.604, p=0.000), and simultaneous effect (F=106.968, p=0.000, R=0.862), with high satisfaction at 91.83%. In conclusion, service quality and price positively and significantly influence Generation Z ShopeeFood satisfaction both partially and simultaneously; recommendations include enhancing service consistency for loyalty.